2014
DOI: 10.3109/10826084.2014.935792
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Parent Support Trajectories and Substance Use and Misuse among Minority Urban Adolescents: A Latent Class Growth Analysis

Abstract: We sought to examine latent classes of family functioning and parent support trajectories during high school and whether these trajectories are associated with an increased risk of substance use and misuse among urban youth. A total of 850 adolescents (Mage = 15.1 years) were included in this study, assessed at baseline, 12-, 24-, and 36-months postbaseline, and completed self-report measures on past 30-day alcohol and marijuana use, binge drinking, and measures of family functioning and parent support. Latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
2
22
0
4
Order By: Relevance
“…Finally, only adolescent reports of family functioning were used in this study. Given that the family is a system, and different members of the family system may have different perspectives with regard to how well (or poorly) the family functions, applying the parent–adolescent discrepancy methodology may be useful to understanding the etiology of sexual risk behaviors and STI (Cordova, Huang et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, only adolescent reports of family functioning were used in this study. Given that the family is a system, and different members of the family system may have different perspectives with regard to how well (or poorly) the family functions, applying the parent–adolescent discrepancy methodology may be useful to understanding the etiology of sexual risk behaviors and STI (Cordova, Huang et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…While we viewed delinquent behavior with a developmental perspective, we tested risk factors and protective factors as static factors in this study. However, it is possible that people move in and out of poverty over time (Mistry et al 2002), and other factors also could be varying during the assessment period (e.g., family functioning, Cordova et al 2014; positive youth development; Lewin-Bizan et al 2010b). The lack of inquiry into such dynamics may be one of the reasons for weak longitudinal effects observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One such risk factor is family or parent dysfunction (Fergusson and Horwood 1997; Kamon et al 2006). Consistent with this view, prior research has consistently found that problems with parenting processes such as monitoring, communication, and closeness with the child are important risk factors for the development and maintenance of adolescent SU (see Vakalahi 2001; Cordova et al 2014; Marceau et al 2015). …”
Section: Introductionmentioning
confidence: 73%